An inventory model for deteriorating items with expiry date and time varying holding cost. (2018) - Sharma, Seema; Singh, Sanjay; Singh, S.R.
In this paper, an economic order quantity model for items which deteriorate and expire with time has been developed. The holding cost has been assumed to be a linear function of time, whereas demand has been considered as a function of expiry date and selling price. Shortages are allowed and partially backlogged. The model so developed has been discussed for two cases of partial backlogging: 1) backlogging rate is taken to be constant; 2) backlogging rate depends upon waiting time. A numerical example given here illustrates each case. Finally, sensitivity analysis is carried out to analyse the behaviour of the model.